Karakteristik Dan Model Pendidikan Bagi Anak Tuna Daksa - Syarief, Natasya Salsabilla; Pangestu, Andre an; Putri, Hesti Klatina; Filkhaqq, Tsin’yanul Arsyi; Harjanti, Ghaida Yasmin Nur (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2022)
Every child is born in different conditions. There are children who are born with physical disabilities or are called physically disabled. Education for children with physical disabilities is no different from children who do not have physical disabilities. However, children with disabilities need special attention from teachers and parents. Children with physical disabilities have slightly different characteristics from normal children. In the learning process, special services are needed for children with disabilities. The purpose of this journal is to determine the characteristics of children with disabilities and education for children with disabilities. The method used in this journal is the library method which is sourced from articles, journals, books related to knowing the characteristics of children with disabilities and education for children with disabilities.